GYY4137 and Sodium Hydrogen Sulfide Relaxations Are Inhibited by L-Cysteine and KV7 Channel Blockers in Rat Small Mesenteric Arteries - Abramavicius, Silvijus; Petersen, Asbjørn G.; Renaltan, Nirthika S.; Prat-Duran, Judit; Torregrossa, Roberta; Stankevicius, Edgaras; Whiteman, Matthew; Simonsen, Ulf (Frontiers in Pharmacology, 2021)
Donors of H2S may be beneficial in treating cardiovascular diseases where the plasma levels of H2S are decreased. Therefore, we investigated the mechanisms involved in the relaxation of small arteries induced by GYY4137 ((4-methoxyphenyl)-morpholin-4-yl-sulfanylidene-sulfido-λ5-phosphane;morpholin-4-ium), which is considered a slow-releasing H2S donor. Sulfides were measured by use of 5,5’-dithiobis-(2-nitro benzoic acid), and small rat mesenteric arteries with internal diameters of 200-250 µm were mounted in microvascular myographs for isometric tension recordings. GYY4137 produced similar low levels of sulfides in the absence and the presence of arteries. In U46619-contracted small mesenteric arteries, GYY4137 (10-6-10-3 M) induced concentration-dependent relaxations, while a synthetic, sulfur-free, GYY4137 did not change the vascular tone. L-cysteine (10-6-10-3 M) induced only small relaxations reaching 24±6% at 10-3 M. Premixing L-cysteine (10-3 M) with Na2S and GYY4137 decreased Na2S relaxation and abolished GYY4137 relaxation, an effect prevented by a nitric oxide (NO) synthase inhibitor, L-NAME (Nω-nitro-L-arginine methyl ester). In arteries without endothelium or in the presence of L-NAME, relaxation curves for GYY4137 were rightward shifted. High extracellular K+ concentrations decreased Na2S and abolished GYY4137 relaxation suggesting potassium channel-independent mechanisms are also involved in Na2S relaxation while potassium channel activation is pivotal for GYY4137 relaxation in small arteries. Blockers of large-conductance calcium-activated (BKCa) and voltage-gated type 7 (KV7) potassium channels also inhibited GYY4137 relaxations. The present findings suggest that L-cysteine by reaction with Na2S and GYY4137 and formation of sulfides inhibits relaxations by these compounds. The low rate of release of H2S species from GYY4137 is reflected by the different sensitivity of these relaxations towards high K+ concentration and potassium channel blockers compared with Na2S. The perspective is that the rate of release of sulfides plays an important for the effects of H2S salt versus donors in small arteries, and hence for a beneficial effect of GYY4137 for the treatment of cardiovascular disease.